Hormone Levels and Sexual Functioning After Risk-Reducing Salpingo-Oophorectomy - Nora Johansen, MD; Astrid H. Liavaag, MD, PhD; Lars Mørkrid, MD, PhD; Trond M. Michelsen, MD, PhD (Sexual Medicine, 2018)
Introduction: Women after risk-reducing salpingo-oophorectomy (RRSO) can have impaired sexual functioning, but whether there is an association between hormone levels and sexual functioning is unclear. Aim: To determine whether hormone levels are associated with sexual functioning in women after RRSO. Methods: This is a retrospective cohort study of 198 sexually active and 91 inactive women after RRSO. Participants completed the Sexual Activity Questionnaire, questionnaires concerning hormone replacement therapy (HRT), quality of life, care from partner, body image, and comorbidity and provided blood samples. Associations between sexual functioning scores and covariates were examined by linear regression. Variables associated with sexual activity were examined by logistic regression. Main Outcome Measures: Associations with sexual pleasure and sexual discomfort scores were expressed by multivariable regression coefficients and associations with sexual activity were expressed by odds ratios. Results: None of the hormone levels were associated with sexual pleasure in contrast to age (P = .032), current use of systemic HRT (P = .002), and more care form partner (P < .001). Increased free androgen index (P = .016), more care from partner (P = .017), systemic HRT (P = .002), and no history of cardiovascular disease (P = .001) were associated with less sexual discomfort. The odds ratio of being sexually active increased with younger age, no breast cancer, better quality of life, and more care from partner. Conclusions: Our results indicate that other factors than hormone levels are important for sexual functioning, although systemic HRT can have a positive impact on sexual functioning in women who have undergone RRSO. Testosterone therapy could improve women's sexual functioning after RRSO; however, the inverse association between free androgen levels and sexual discomfort should be addressed in future studies.Johansen N, Liavaag AH, Mørkird L, Michelsen TM. Hormone Levels and Sexual Functioning After Risk-Reducing Salpingo-Oophorectomy. Sex Med 2018;6:143–153. Key Words: BRCA1 Gene, BRCA2 Gene, Ovariectomy, Hormones, Sexuality, Hormone Replacement Therapy